Glassy ionogels with high compressibility and strength for impact protection - Jiayu Wang; Shilong Zhang; Lingling Li; Xiaoliang Wang; Jiaofeng Xiong; Qingning Li; Weizheng Li; Feng Yan (Proceedings of the National Academy of Sciences, 2025)
Solvents within gels enhance the mobility of polymer chain segments while concurrently diminishing interchain interactions, thereby facilitating the ductility of glassy polymers at the cost of their mechanical strength. Here, we develop a solvent toughening strategy for the preparation of highly compressible and high-strength ionogels in the glassy state. This approach leverages the synergistic effects of the slow dissociation-shift kinetics of solvent ionic liquids and polymer crystallization. Ionogels exhibit an ultimate compressive stress of 2.3 GPa (at 98% compressive strain), toughness of 1219.3 MJ m −3 , and energy dissipation rate of 81.9% (at 70% compression strain). The highly interacting ionic bonds of solvent and the fast crystallization of polymers under load toughen the ionogels and confer impact hardening and efficient energy dissipation behavior under fast impact. A 500-μm-thick ionogel coating can protect fragile items, such as glass, from impact damage. Ionogels, renowned for their impact resistance, hold promise for various applications across industries including human body implants, equipment, transportation, and aerospace.